PENGARUH KUALITAS AUDIT DAN EFEKTIVITAS KOMITE AUDIT TERHADAP PENGUNGKAPAN SUKARELA DI BURSA EFEK INDONESIA - Gizta, Aulia Dewi; Enjelina, Enjelina; Afriyadi, Afriyadi; Sambodo, Bambang; Lidya, Marina (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The era of globalization has triggered a global crisis which has caused a number of companies and public accounting services to begin to doubt their credibility and consider them. Therefore, disclosure of information in the company's financial reports plays an important role. This research aims to examine the influence of audit quality and audit committee effectiveness on voluntary disclosure in property companies listed on the Indonesia Stock Exchange (BEI). This research uses quantitative methods. The objects of this research are property companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. The sampling method was purposive sampling method so that a sample of 39 companies was obtained. The research results show that the Audit Quality variable partially influences Voluntary Disclosure. Meanwhile, the Audit Committee Effectiveness variable has no effect on Voluntary Disclosure. Then, simultaneously, Audit Quality and Audit Committee Effectiveness influence the Voluntary Disclosure.